Tackling Social Problems in Branches Muhammadiyah Porong - Juwita Ika Puspita Dewi; Eva Yulia Efendy; Mar’atus Solichah; Ilmiatul Hidayanti; Nurvita Putri Utami (International Consortium of Education and Culture Research Studies, 2020)
The purpose of this study was to determine social problems in the Porong Muhammadiyah branch and its remedies, and to find out the history of the establishment of the Muhammadiyah branch in Porong. This research is a descriptive qualitative research through interviews and direct observations on the chairman of Muhammadiyah Porong. Based on the results of research on social problems in Muhammadiyah Porong along with the history of the establishment of Muhammadiyah Porong, it was established in 1965 when the age is quite old until now, during the Lapindo mud disaster, as a result various social problems occurred, namely experiencing a lot of decline and the impact both from the social side social, from an economic standpoint, in terms of life diversity is very influential, because many residents have moved villages but remain in the Porong region and some have moved outside the Porong sub-district. As a result of the social impact of Lapindo mud, there is a demoralization and even crime and crime, then the spirit of life of people to practice the religion has decreased, even ethical values, spiritual values ​​have declined due to the Lapindo mud disaster. Therefore, the efforts of Muhammadiyah Porong, especially for Muhammadiyaah and Aisha residents, including their parents, first continue to carry out spiritual activities such as studies, guidance, understanding of religion, then from an economic standpoint, because almost 80% of the people in Porong are traders and merchants. who became very few farmers, because the life of the Porong community was almost a trader and a merchant, one of his da'wah was how to become an Islamic trader, honest, not cheating, really running a trade that did not harm others. In the field of education is much better, physically very good than those in the village of Mindi because the current building in the village of Lajuk is much better and wider.